Establishment of an induced pluripotent stem cell line (SDCHi011-A) from a healthy Chinese female donor - Shuyun Wang; Qian Zeng; Mengmeng Chen; Haiyan Zhang; Xin Lv (Stem Cell Research)
We generated an induced pluripotent stem cell (iPSC) line from peripheral blood mononuclear cells (PBMCs) of a healthy 40-year-old Chinese Han female, using non-integrated reprogramming technology. The established iPSC line, SDCHi011-A, expressed pluripotency marker and could differentiate into cells of three germ layers in vitro with normal karyotype. This cell line is a valuable resource as a control line for stem cell research of disease models and molecular pathogenesis.